Analisis Perkembangan Janin dan Pendidikan Prenatal Islam: Kajian Integratif Embriologi dan Teks Keislaman - Ermis Suryana; Zulhijra; Fitri Anggraini (Universitas Muhammadiyah Makassar, 2026)
This study analyzes the correlation between the stages of fetal development from an Islamic perspective and modern embryology findings, as well as its implications for prenatal education. Employing a qualitative method with a library research approach, this study collects secondary data from the Quran, Hadith, tafsir (Quranic exegesis), and scientific literature on embryology and prenatal neuroscience. The data were analyzed using content analysis and comparative techniques. The findings reveal a significant correspondence between Quranic embryological terms (nuthfah, ‘alaqah, mudghah) and the stages of fetal development in modern embryology. Contemporary neuroscience research also supports Islamic prenatal education practices, such as Quranic recitation, dhikr, verbal communication with the fetus, and maintaining the mother’s positive psycho-spiritual well-being.This study concludes that integrative Islamic prenatal education — encompassing spiritual, psychological, physical, and social dimensions — can optimize the holistic development of the fetus. Recommendations include the development of standardized Islamic prenatal education curricula, training programs for healthcare professionals, and further empirical research to measure the effectiveness of these interventions on children’s postnatal development. Keywords: Fetal Development, Islamic Prenatal Education, Qur’anic Embryology, Prenatal Neuroscience